1999
DOI: 10.1042/cs0960271
|View full text |Cite
|
Sign up to set email alerts
|

Venous duplex scanning of the leg: range, variability and reproducibility

Abstract: Despite the many studies on venous haemodynamics using duplex, only a few evaluated the normal values, variability and reproducibility. Therefore, the range and variability of venous diameter, compressibility, flow and reflux were measured. To obtain normal values, 42 healthy individuals (42 limbs, 714 vein segments) with no history of venous disease were scanned by duplex. To determine the reproducibility the intra-observer variability was measured in 11 healthy individuals (187 vein segments) and the inter-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 23 publications
3
21
0
Order By: Relevance
“…They found an interobserver variability coefficient for compressibility equal to 0.77, whereas according to reflux it was calculated as equal to 0.86 13. Such good results are in agreement with other previous papers,14 and pointed out the need for the correct setting of ultrasound machines, in order to achieve better results in the definition of the images, and in their reproducibility 15.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…They found an interobserver variability coefficient for compressibility equal to 0.77, whereas according to reflux it was calculated as equal to 0.86 13. Such good results are in agreement with other previous papers,14 and pointed out the need for the correct setting of ultrasound machines, in order to achieve better results in the definition of the images, and in their reproducibility 15.…”
Section: Discussionsupporting
confidence: 85%
“…Interesting findings came from Haenen et al13 They tried to evaluate interobserver variability coefficients of common duplex ultrasound in patients previously diagnosed with deep venous thrombosis. They found an interobserver variability coefficient for compressibility equal to 0.77, whereas according to reflux it was calculated as equal to 0.86 13.…”
Section: Discussionmentioning
confidence: 99%
“…Pathological reflux was defined as a reversed flow duration of more than 1 s in the proximal veins and more than 0.5 s in the distal veins. The kappa of the interobserver variability was 0.86 [12].…”
Section: Methodsmentioning
confidence: 93%
“…Both VOR and duplex are non-invasive tests with a good interobserver variability and can easily be used in studies and usual patient care [12,14]. Previously we demonstrated that the measurement of TS, VOR and reflux at three months follow-up can be used as a proxy or surrogate endpoint for PTS [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation